Beyond the bubble test : how performance assessments support 21st century learning - Darling-Hammond, Linda, 1951- (Jossey-Bass & Pfeiffer Imprints, Wiley, 2014)
Educators are unhappy with the current assessments and their focus on low-level skills like recalling and restating facts rather than higher-order skills such as problem-solving and analyzing and synthesizing information. This book examines performance assessment as an alternative to the current high stakes standardized testing system in theUnites States. A must-have resource for those interested in the current research of performance assessment in the 21st century, this book will help educators accurately assess the benefits and possibilities for adopting performance assessments nation ...